2014
DOI: 10.1177/1098612x14522051
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of aural microflora in healthy cats, allergic cats and cats with systemic disease

Abstract: Twenty healthy cats (group 1) with clinically normal ears, 15 cats with systemic disease (group 2) and 15 allergic cats (group 3) were included in a prospective study. The experimental unit was the ear. A clinical score was established for each ear canal after otoscopic examination. Microbial population was assessed on cytological examination of smears performed with the cotton-tipped applicator smear technique. Fungal population was significantly more prominent in allergic cats (P <0.001) and in diseased cats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…To the best of our knowledge, there have not been any recent studies investigating the prevalence of O cynotis in a large cohort of cats in the UK, and there have been only three studies that have evaluated the normal external ear cytology in cats. 5,6,12 This study found that the prevalence of O cynotis was low, recorded as 0.9%. This result is in agreement with a Belgian study (2%), 10 an Australian study (<0.1%) 13 and a Portuguese study (2.2%).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…To the best of our knowledge, there have not been any recent studies investigating the prevalence of O cynotis in a large cohort of cats in the UK, and there have been only three studies that have evaluated the normal external ear cytology in cats. 5,6,12 This study found that the prevalence of O cynotis was low, recorded as 0.9%. This result is in agreement with a Belgian study (2%), 10 an Australian study (<0.1%) 13 and a Portuguese study (2.2%).…”
Section: Discussionmentioning
confidence: 72%
“…24 Previous studies have found very different values for aural Malassezia organism counts in normal cats. 5,6,12 Two studies used the × 40 objective for examining each highpower field. 5,6 In our study, similar to a previous study, 12 we used the × 100 oil immersion objective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contast, another study failed to identify yeasts in 20 health cats sampled in France; notably in the latter study, the presence of cerumen was an exclusion criterion whereas cerumen was noted in many of the US cats, especially amongst those with a purely indoor lifestyle . Malassezia yeasts were detected in 20% (six of 30) ear canals of 15 cats with disease and in 43% (13 of 30) ear canals of 15 allergic cats . Devon rex cats and sphynx cats, but not Cornish rex cats, are prone to high carriage rates of Malassezia yeasts and a generalised seborrhoeic dermatitis that responds to oral itraconazole .…”
Section: Ecology and Epidemiologymentioning
confidence: 98%
“…Outros casos de meningite relacionados com infecção do trato respiratório também já foram relatados [6], inclusive com resistência à doxiciclina e tetraciclina [2]. De acordo com o laudo bacteriológico, a bactéria isolada da bula timpânica condiz com a microbiota presente nos casos de otite média e interna em gatos [17].…”
Section: Discussionunclassified